2001
DOI: 10.1007/s003300000598
|View full text |Cite
|
Sign up to set email alerts
|

Endorectal magnetic resonance imaging of prostatic cancer: comparison between fat-suppressed T2-weighted fast spin echo and three-dimensional dual-echo, steady-state sequences

Abstract: The aim of this study was to develop an endorectal MRI strategy for prostatic cancer. We evaluated the MR images from 44 consecutive prostatic cancer patients treated by radical prostatectomy. Each sequence from every examination was assessed separately with a specific tumor map drawn. Tumor localization, capsular penetration, and seminal vesicle invasion were marked on maps on the basis of T2 and DESS (dual-echo steady-state) sequences. Thirty patients also had T1-weighted images, and these were assessed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 15 publications
3
30
0
Order By: Relevance
“…Ikonen et al 8 showed that 77% of the patients had visible hemorrhage on endorectal magnetic resonance imaging after a single biopsy, and found that it took 28 days for a radiologically obvious decrease in the amount of blood. This postbiopsy hemorrhage can lead to periprostatic inflammation and fibrosis, obliterating surgical planes of dissection, and making a future operation more technically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Ikonen et al 8 showed that 77% of the patients had visible hemorrhage on endorectal magnetic resonance imaging after a single biopsy, and found that it took 28 days for a radiologically obvious decrease in the amount of blood. This postbiopsy hemorrhage can lead to periprostatic inflammation and fibrosis, obliterating surgical planes of dissection, and making a future operation more technically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) has gained clinical acceptance in the preoperative evaluation of prostatic carcinoma patients in terms of extracapsular spread, seminal vesicle-neurovascular bundle invasion, lymph node metastases in patients with biopsy proven prostatic carcinoma [1]. On the other hand, the accuracy of T2-weighted sequences in the diagnosis of prostate cancer is limited, due to lack of sensitivity and specificity [2,3]. Both prostatitis and tumoral infiltration have overlapping features and are seen as decreased signal intensity foci on conventional T2-weighted images [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these results are valid only for examinations performed with a phased-array coil and that they cannot be extrapolated to examinations performed with an endorectal coil. Approximately 70% of cases in prostate cancer arise in the peripheral zone [24], and the accuracy of tumor detection for cancers originating in the peripheral zone using MR imaging is reported to be approximately 50-70% [7,8,9,10]. The remaining prostate cancer cannot be detected because the lesions were essentially isointense to the peripheral zone [25].…”
Section: Discussionmentioning
confidence: 99%
“…The most cancer nodules arise in the peripheral zone and are of low signal intensity compared with an inherently high signal intensity of the peripheral zone by this method. Since 512 matrix can be used in T2-weighted FSE imaging either with body coil or endorectal surface coil, high spatial resolution is obtained with a short acquisition time; however, the limitation of conventional or FSE imaging also exists and 30-40% of prostate cancer in the peripheral zone are undetectable because the lesions are isointense to the peripheral zone [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%